Transparent Conductive Film

The transparent conductive film with a laminated structure of zinc oxide, silver, and indium oxide layers addresses conductivity and silver aggregation issues, providing high conductivity, moisture resistance, and flexibility, suitable for display and solar cell applications.

JP7608702B2Active Publication Date: 2025-01-07OIKE & CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022173639
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-12-15
Filing Date
2022-10-28
Publication Date
2025-01-07
Estimated Expiration
2042-10-28

AI Technical Summary

Technical Problem

Existing transparent conductive films face issues with high conductivity, susceptibility to cracking, impaired flexibility, and increased cost due to thickness, and silver aggregation in laminated structures, which affects heat and humidity resistance and photoelectric conversion efficiency.

Method used

A transparent conductive film with a laminated structure comprising a base material, a first metal oxide layer of zinc oxide and tin oxide, a metal layer of silver or silver alloy, and a second metal oxide layer of indium oxide and tin oxide, designed to maintain an amorphous state and prevent silver aggregation, ensuring high conductivity and moisture resistance.

Benefits of technology

The film achieves excellent conductivity, heat and moisture resistance, and maintains flexibility while reducing manufacturing costs, with improved transparency and adhesion, suitable for display and solar cell applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608702000005
    Figure 0007608702000005
  • Figure 0007608702000006
    Figure 0007608702000006
  • Figure 0007608702000007
    Figure 0007608702000007
Patent Text Reader

Abstract

To provide a transparent conductive film excellent in conductivity and moisture heat resistance.SOLUTION: There is provided a transparent conductive film which has a base material, a first metal oxide layer, a metal layer and a second metal oxide layer in this order, wherein the first metal oxide layer contains zinc oxide and tin oxide, the metal layer contains at least any of silver and a silver alloy, the second metal oxide layer contains indium oxide and tin oxide and when the transparent conductive film after subjecting to heat treatment at 150°C for 30 minutes is measured by an X-ray crystal diffraction method, no peak is detected in 2θ=29° to 32°.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transparent conductive film. [Background technology]

[0002] Currently, transparent conductive films are used in a variety of products, including touch panels, electronic paper, liquid crystal displays, and RF-ID tags. Transparent conductive films include those made of a thin film of ITO, which is made of indium oxide and tin oxide, but higher conductivity is required for solar cells, organic electroluminescence (EL) films, electromagnetic wave shielding, EC light control sheets, and transparent electrodes for large-area displays.

[0003] To obtain high conductivity from a thin ITO film, in addition to optimizing carrier density and mobility, a film thickness several times thicker than that used in small touch panels is required. However, as the film thickness increases, the ITO thin film becomes more susceptible to cracking and its flexibility is compromised. In addition, increased processing time inevitably leads to higher costs. In order to achieve high conductivity, a transparent electrode using a silver alloy with low resistivity has been proposed in which thin layers of a metal oxide, a silver alloy, and a metal oxide are laminated in this order (metal oxide / silver alloy / metal oxide) (see, for example, Patent Document 1). This transparent electrode uses a silver alloy with a carrier density one order of magnitude higher than that of ITO, which allows for high conductivity while reducing the average thickness of the metal oxide / silver alloy / metal oxide laminate, thereby improving flexibility and reducing manufacturing costs. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-15623 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, in the technology disclosed in Patent Document 1, in an electrode having a layered structure of metal oxide / silver alloy / metal oxide, the silver alloy is sandwiched between layers of the same metal oxide, such as ITO, and there is a problem in that the silver in the silver alloy is likely to agglomerate due to water vapor that has permeated the metal oxide, which may result in a decrease in moist heat resistance. Furthermore, aggregation of silver not only deteriorates the appearance and makes it difficult to use the film for display purposes, but also poses the problem of reduced photoelectric conversion efficiency in solar cells and the like. In view of these problems, it is very important to suppress the aggregation of silver.

[0006] The present invention aims to solve the above-mentioned problems in the prior art and to achieve the following object: That is, the present invention aims to provide a transparent conductive film having excellent electrical conductivity and resistance to moist heat. [Means for solving the problem]

[0007] The means for solving the above problems are as follows. <1> A transparent conductive film having a substrate, a first metal oxide layer, a metal layer, and a second metal oxide layer in this order, the first metal oxide layer contains zinc oxide and tin oxide; The metal layer contains at least one of silver and a silver alloy, the second metal oxide layer contains indium oxide and tin oxide; The transparent conductive film is characterized in that, when the transparent conductive film is heat-treated at 150°C for 30 minutes and then measured by X-ray crystal diffraction, no peak is detected at 2θ=29° to 32°. <2> The second metal oxide layer has an arithmetic mean roughness Ra of 15 nm or less. <1> 2. The transparent conductive film according to claim 1 . <3> The content of tin oxide in the second metal oxide layer is 5 mass % or more with respect to the total amount of the indium oxide and the tin oxide. <1> or <2> 2. The transparent conductive film according to claim 1 . <4> The total light transmittance measured according to JIS K7361-1 is 82% or more. <1> from <3> 1. The transparent conductive film according to claim 1, Effect of the Invention

[0008] According to the present invention, the above-mentioned problems in the prior art can be solved, the above-mentioned objects can be achieved, and a transparent conductive film having excellent electrical conductivity and moist heat resistance can be provided. [Brief description of the drawings]

[0009] [Figure 1A] FIG. 1A is a cross-sectional view showing an example of the transparent conductive film of the present invention. [Figure 1B] FIG. 1B is a cross-sectional view showing another example of the transparent conductive film of the present invention. [Figure 2A] FIG. 2A is a diagram showing the measurement results of the transparent conductive film of Example 1 by X-ray crystal diffraction method. [Figure 2B] FIG. 2B is a diagram showing the measurement results of the transparent conductive film of Example 2 by X-ray crystal diffraction method. [Figure 2C] FIG. 2C is a diagram showing the measurement results of the transparent conductive film of Example 3 by X-ray crystal diffraction method. [Figure 2D] FIG. 2D is a diagram showing the measurement results of the transparent conductive film of Comparative Example 1 by X-ray crystal diffraction method. [Figure 2E] FIG. 2E is a diagram showing the measurement results of the transparent conductive film of Comparative Example 2 by X-ray crystal diffraction method. [Figure 2F] FIG. 2F is a diagram showing the measurement results of the transparent conductive film of Comparative Example 3 by X-ray crystal diffraction method. [Figure 2G] FIG. 2G is a diagram showing the measurement results of the transparent conductive film of Comparative Example 4 by X-ray crystal diffraction method. [Figure 2H] FIG. 2H is a diagram showing the measurement results of the transparent conductive film of Comparative Example 5 by X-ray crystal diffraction method. [Figure 2I]FIG. 2I is a diagram showing the measurement results of the transparent conductive film of Comparative Example 6 by X-ray crystal diffraction method. [Figure 2J] FIG. 2J is a diagram showing the measurement results of the transparent conductive film of Comparative Example 7 by X-ray crystal diffraction method. [Figure 2K] FIG. 2K is a diagram showing the measurement results of the transparent conductive film of Comparative Example 8 by X-ray crystal diffraction method. [Figure 2L] FIG. 2L shows the measurement results of the transparent conductive film of Comparative Example 9 by X-ray crystal diffraction method. [Figure 2M] FIG. 2M is a diagram showing the measurement results of the transparent conductive film of Comparative Example 10 by X-ray crystal diffraction method. [Figure 2N] FIG. 2N is a diagram showing the measurement results of the transparent conductive film of Comparative Example 11 by X-ray crystal diffraction method. [Figure 2O] FIG. 2O is a diagram showing the measurement results of the transparent conductive film of Comparative Example 12 by X-ray crystal diffraction method. [Figure 2P] FIG. 2P is a diagram showing the measurement results of the transparent conductive film of Example 4 by X-ray crystal diffraction method. [Figure 2Q] FIG. 2Q is a diagram showing the measurement results of the transparent conductive film of Example 5 by X-ray crystal diffraction method. [Figure 3A] FIG. 3A is a photograph showing the appearance of the transparent conductive film of Example 1 after a moist heat resistance test (60° C., 95% RH, 250 hours). [Figure 3B] FIG. 3B is a photograph showing the appearance of the transparent conductive film of Example 1 after a moist heat resistance test (80° C., 85% RH, 250 hours). [Figure 3C] FIG. 3C is a photograph showing the appearance of the transparent conductive film of Comparative Example 5 after a moist heat resistance test (60° C., 95% RH, 250 hours). [Figure 3D] FIG. 3D is a photograph showing the appearance of the transparent conductive film of Comparative Example 5 after a moist heat resistance test (80° C., 85% RH, 250 hours). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] (Transparent conductive film) The transparent conductive film of the present invention has a substrate, a first metal oxide layer, a metal layer, and a second metal oxide layer in this order, the first metal oxide layer contains zinc oxide and tin oxide; The metal layer contains at least one of silver and a silver alloy, The second metal oxide layer contains indium oxide and tin oxide, and may further include other layers as required. In the transparent conductive film of the present invention, when the transparent conductive film is heat-treated at 150° C. for 30 minutes and then measured by X-ray crystal diffraction, no peak is detected at 2θ=29° to 32°.

[0011] In a transparent conductive film having a laminated structure having a substrate, a first metal oxide layer, a metal layer, and a second metal oxide layer in this order, the second metal oxide layer is arranged so as to be exposed. Therefore, in order to improve the conductivity of the transparent conductive film, it is desirable that the conductivity (surface resistance) of the second metal oxide layer itself is good. Depending on the application of the transparent conductive film, a heat treatment may be required in the post-treatment. In this case, the material of the first and second metal oxide layers may be crystallized by the heat treatment to generate crystal grain boundaries, which may create a passageway for outside air containing water vapor in the first and second metal oxide layers, and the water vapor may cause aggregation of silver in the metal layer. For this reason, the present inventors have found that it is important for the first and second metal oxide layers to have a property of being able to maintain an amorphous state over time or even after heat treatment.

[0012] The inventors have discovered that in a transparent conductive film having a laminated structure comprising, in this order, a substrate, a first metal oxide layer, a metal layer, and a second metal oxide layer, the metal layer contains at least one of silver and a silver alloy, and the second metal oxide layer contains indium oxide and tin oxide, it is possible to achieve both excellent electrical conductivity and moist heat resistance. In particular, the inventors have found that: (1) excellent conductivity can be achieved by combining a metal layer with a high carrier concentration and a second metal oxide layer with a low surface resistance; and (2-1) a first metal oxide layer that is difficult to crystallize and contains zinc oxide and tin oxide, although having a high surface resistance itself, is disposed on the substrate side, and (2-2) by disposing an amorphous second metal oxide layer, excellent moisture and heat resistance (barrier function) based on the amorphous state in the first and second metal oxide layers can be exhibited. Regarding the second metal oxide layer containing indium oxide and tin oxide, whether it "can maintain an amorphous state even over time or after heat treatment" can be confirmed by whether a peak appears at 2θ = 29° to 32° corresponding to the (222) plane of ITO in the second metal oxide layer by X-ray diffraction method after performing a heat treatment (acceleration test) under the conditions of 150°C for 30 minutes. If a peak appears at 2θ = 29° to 32°, it means that crystallization has occurred by the acceleration test, and it can be determined that it has a property (film quality) that is prone to crystallization over time. Conversely, if no peak appears at 2θ = 29° to 32°, it means that crystallization has not occurred even after the acceleration test, and it can be determined that it has a property (film quality) that is difficult to crystallize over time.

[0013] The absence of a peak at 2θ = 29° to 32° corresponding to the (222) plane of ITO in the second metal oxide layer containing indium oxide and tin oxide can be determined based on the measurement results of the X-ray diffraction method. Specifically, it can be confirmed by the following method. First, perform the X-ray diffraction method under the following conditions. <Measurement conditions of X-ray diffraction method> · Apparatus name: X-ray diffractometer (XRD6100, manufactured by Shimadzu Corporation) · Standard mode · X-ray source: CuKα · Tube voltage: 40 kV · Tube current: 30 mA · Drive axis: 2θ / θ · Scanning speed: 2.00° / min Scan step: 0.02° Scanning range: Measures diffraction intensity from 29° to 32° Goniometer: Vertical Divergence slit: 1° Scattering slit: 1° Receiving slit: 0.30mm Then, based on the raw measured data, the following values ​​are calculated: <1> ~ <3> Calculate. <1> Maximum diffraction intensity in the range of 30° to 31° <2> The diffraction intensity at 29° and 32° is added and divided by 2 <3> <1> of <2> Divided by " <1> The "maximum value of the diffraction intensity in the range of 30° to 31°" is higher when the ITO in the second metal oxide layer is crystallized than when the ITO is not crystallized. Also," <1> When the ITO in the second metal oxide layer is not crystallized, the "maximum value of the diffraction intensity in the range of 30° to 31°" is " <2> The value is close to the sum of the diffraction intensities at 29° and 32° divided by 2. For this reason, in the present invention, <3> <1> of <2> If the value of "Divide by" is 1.2 or more, it is judged that "a peak has been detected" and <3> <1> of <2> When the value obtained by dividing the peak by the mean value is less than 1.2, it is determined that "no peak is detected."

[0014] In the present invention, "transparent" means that the haze value measured according to JIS K7136 is 15% or less. The haze value of the transparent conductive film of the present invention measured according to JIS K7136 is preferably 6% or less, more preferably 4% or less, and even more preferably 2% or less. When the haze value is 6% or less, the film can be suitably used for display applications. In the transparent conductive film of the present invention, the total light transmittance (visible light transmittance) measured in accordance with JIS K7361-1 is preferably 78% or more, more preferably 80% or more, and even more preferably 82% or more. When the total light transmittance is 78% or more, a transparent conductive film having excellent transparency can be obtained, and the film can be suitably used in applications requiring high visible light transmittance, such as displays and solar cells. The haze value and the total light transmittance are not particularly limited and can be appropriately selected depending on the purpose. For example, they can be measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., model number: NDH5000SP).

[0015] The surface resistance value of the transparent conductive film of the present invention is preferably 30 Ω / □ or less, more preferably 20 Ω / □ or less, and even more preferably 15 Ω / □ or less. The surface resistance value may be measured, for example, at any 10 points using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech Co., Ltd., model number: MCP-T610) and the average value may be calculated.

[0016] <Base material> The base material is a material that serves as a substrate for the transparent conductive film of the present invention.

[0017] The shape, structure and size of the substrate are not particularly limited and may be appropriately selected depending on the purpose.

[0018] The material of the substrate is not particularly limited and can be appropriately selected depending on the purpose. Examples of the material include poly(meth)acrylic acid esters such as polymethyl methacrylate (PMMA), polycarbonate, polyethylene terephthalate (PET), polyethylene-2,6-naphthalate (PEN), cycloolefin polymer (COP), triacetyl cellulose (TAC), polyether ether ketone (PEEK), liquid crystal polymer (LCP), transparent polyimide (CPI), and the like.

[0019] The average thickness of the substrate is preferably 6 μm or more and 300 μm or less, more preferably 12 μm or more and 250 μm or less, and even more preferably 25 μm or more and 200 μm or less. When the average thickness of the substrate is 6 μm or more, the handling property during processing can be improved. In addition, when the average thickness of the substrate is 300 μm or less, a flexible transparent conductive film can be obtained. The average thickness of the substrate can be determined by measuring the thickness at any five points using an electronic micrometer (manufactured by Anritsu Corporation, device name: KG3001A) and calculating the average value.

[0020] The total light transmittance of the substrate measured in accordance with JIS K7361-1 is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. When the total light transmittance is 60% or more, the transparency of the transparent conductive film can be improved. The total light transmittance is not particularly limited and may be appropriately selected depending on the purpose. For example, it may be measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., model number: NDH5000SP).

[0021] In addition, the haze value of the substrate measured according to JIS K7136 is preferably 6% or less, more preferably 4% or less, and even more preferably 2% or less. When the haze value is 6% or less, the transparency of the transparent conductive film can be improved. When the haze value is 2% or less, the transparent conductive film of the present invention can be suitably used for display applications. The haze value is not particularly limited and can be appropriately selected depending on the purpose. For example, it can be measured by a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., device name: NDH5000SP).

[0022] Other characteristics of the substrate include, for example, smoothness.

[0023] An example of an index of the smoothness of the substrate is the arithmetic mean roughness Ra of the surface of the substrate. The arithmetic mean roughness Ra of the surface of the substrate is preferably 50 nm or less, more preferably 30 nm or less, and even more preferably 20 nm or less. When the arithmetic mean roughness Ra of the surface of the substrate is 50 nm or less, the occurrence of defects (gaps due to surface unevenness) in the first metal oxide layer and the second metal oxide layer described below can be suppressed, and the intrusion of water vapor that causes the aggregation of silver can be suppressed. The arithmetic mean roughness Ra of the surface of the substrate can be measured, for example, by an optical interference type surface profile roughness meter (manufactured by Bruker Japan, WYKO ContourGT K1M, measurement conditions: VSI mode).

[0024] <First metal oxide layer> The first metal oxide layer is disposed between the substrate and a metal layer, which will be described later.

[0025] The shape, structure and size of the first metal oxide layer are not particularly limited and can be appropriately selected depending on the purpose.

[0026] The material of the first metal oxide layer contains zinc oxide and tin oxide, and further contains other components as necessary. When the first metal oxide layer contains zinc oxide and tin oxide, an amorphous film having no crystal grain boundaries can be obtained, and the film can be made less permeable to water vapor, which causes aggregation of silver contained in the metal layer. The zinc oxide and tin oxide include, for example, ZTO.

[0027] The content of tin oxide in the zinc oxide and tin oxide is preferably 15% by mass or more and 65% by mass or less, more preferably 20% by mass or more and 60% by mass or less, and even more preferably 25% by mass or more and 55% by mass or less, based on the total amount of zinc oxide and tin oxide. When the content of tin oxide in the zinc oxide and tin oxide is 15% by mass or more, based on the total amount of zinc oxide and tin oxide, a good amorphous film (layer) can be obtained. In addition, when the content of tin oxide in the zinc oxide and tin oxide is 65% by mass or less, based on the total amount of zinc oxide and tin oxide, the moist heat resistance of the first metal oxide layer can be improved.

[0028] The content of the zinc oxide and tin oxide in the first metal oxide layer is preferably 90% by mass or more, and more preferably 95% by mass or more, based on the total amount of the first metal oxide layer. When the content of the zinc oxide and tin oxide in the first metal oxide layer is 90% by mass or more, the total light transmittance can be improved.

[0029] The other components are not particularly limited, and components other than the zinc oxide and tin oxide may be appropriately contained as long as they do not impair the effects of the present invention.

[0030] The average thickness of the first metal oxide layer is preferably 25 nm to 65 nm, more preferably 35 nm to 63 nm, and even more preferably 40 nm to 60 nm. When the average thickness of the first metal oxide layer is 25 nm or more, the effect of suppressing the transmission of water vapor can be improved. Furthermore, when the average thickness of the first metal oxide layer is 65 nm or less, the total light transmittance can be increased. The average thickness (height) of the first metal oxide layer can be measured as follows. First, a substrate on which a first metal oxide layer having a predetermined thickness is formed is prepared, and the physical thickness of the first metal oxide layer having a predetermined thickness is measured by a contact step gauge. The amount of material of the first metal oxide layer in the first metal oxide layer having a predetermined thickness is measured by quantitative analysis using an X-ray fluorescence measurement device (XRF, manufactured by Rigaku Corporation). A calibration curve is created from the thickness measured by the contact step gauge and the amount of material of the first metal oxide layer measured by quantitative analysis using the X-ray fluorescence measurement device (XRF). For a sample to be actually measured, the amount of material of the first metal oxide layer is quantitatively analyzed using the X-ray fluorescence measurement device (XRF), and the thickness is calculated using the created calibration curve. Ten samples are similarly created, and the average value is taken as the average thickness.

[0031] The method for forming the first metal oxide layer is not particularly limited and can be appropriately selected depending on the purpose. For example, the entire surface of the substrate can be treated using various sputtering methods such as DC magnetron sputtering, vapor deposition, and ion plating.

[0032] <Metal layer> The metal layer is disposed between the first metal oxide layer and a second metal oxide layer described below.

[0033] The shape, structure and size of the metal layer are not particularly limited and may be appropriately selected depending on the purpose.

[0034] The material of the metal layer contains at least one of silver and a silver alloy, and further contains other components as required. The metal layer preferably contains a silver alloy, which can improve the effect of suppressing the aggregation of silver. The metal layer may contain silver as a main component, and the silver content in the metal layer is preferably 80% by mass or more and 99.9% by mass or less, more preferably 82% by mass or more and 99.8% by mass or less, and even more preferably 85% by mass or more and 99.7% by mass or less. The silver alloy may contain silver as a main component, and the silver content in the silver alloy is preferably 80% by mass or more and 99.9% by mass or less, more preferably 82% by mass or more and 99.8% by mass or less, and even more preferably 85% by mass or more and 99.7% by mass or less. When the silver content in the silver alloy is 80% by mass or more, the electrical conductivity and optical properties can be improved. When the silver content is 99.9% by mass or less, migration can be suppressed more than with silver alone, and the aggregation of silver can be inhibited. The silver alloy may be, for example, a silver-copper alloy.

[0035] The other components are not particularly limited as long as they do not inhibit the effects of the present invention, and examples thereof include Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Au, Zn, Al, Ga, In, Si, Ge, Sn, Bi, Mn, C, B, N, P, and S.

[0036] The average thickness of the metal layer is preferably 4 nm to 16 nm, more preferably 5 nm to 14 nm, and even more preferably 6 nm to 12 nm. When the average thickness of the metal layer is 4 nm or more, the electrical conductivity can be improved. Also, when the average thickness of the metal layer is 16 nm or less, the total light transmittance can be increased. The average thickness (height) of the metal layer can be measured, for example, as follows. First, a substrate is prepared on which a metal layer having a predetermined thickness is formed, and the physical thickness of the metal layer having the predetermined thickness is measured by a contact step gauge. The amount of material of the metal layer in the metal layer having the predetermined thickness is measured by quantitative analysis using an X-ray fluorescence measurement device (XRF, manufactured by Rigaku Corporation). A calibration curve is created from the film thickness measured by the contact step gauge and the amount of material of the metal layer measured by quantitative analysis using the X-ray fluorescence measurement device (XRF). For the sample to be actually measured, the amount of material of the metal layer is quantitatively analyzed using the X-ray fluorescence measurement device (XRF), and the film thickness is calculated using the created calibration curve. Ten samples are similarly created, and the average value is taken as the average thickness.

[0037] The method for forming the metal layer is not particularly limited and can be appropriately selected depending on the purpose. For example, the method may include treating the entire exposed surface of the first metal oxide layer using various sputtering methods, such as DC magnetron sputtering, vapor deposition, ion plating, etc.

[0038] <Second metal oxide layer> The second metal oxide layer is disposed on the metal layer.

[0039] The shape, structure and size of the second metal oxide layer are not particularly limited and can be appropriately selected depending on the purpose.

[0040] The material of the second metal oxide layer contains indium oxide and tin oxide, and further contains other components as necessary. When the second metal oxide layer contains the indium oxide and tin oxide, the electrical conductivity can be improved. The indium oxide and tin oxide include, for example, ITO.

[0041] The content of tin oxide in the indium oxide and tin oxide is preferably 5% by mass or more, more preferably 5% by mass or more and 14% by mass or less, still more preferably 7% by mass or more and 12% by mass or less, and most preferably 8% by mass or more and 11% by mass or less, based on the total amount of indium oxide and tin oxide. When the content of tin oxide in the indium oxide and tin oxide is 5% by mass or more, the effect of suppressing crystallization can be improved, and the electrical conductivity and moist heat resistance can be improved. Furthermore, when the content of tin oxide in the indium oxide and tin oxide is 14 mass % or less, the total light transmittance can be made excellent.

[0042] The content of the indium oxide and tin oxide in the second metal oxide layer is preferably 95 mass % or more, and more preferably 98 mass % or more, based on the total amount of the second metal oxide layer.

[0043] The other components are not particularly limited, and components other than the indium oxide and tin oxide may be appropriately contained as long as they do not impair the effects of the present invention.

[0044] The average thickness of the second metal oxide layer is preferably 30 nm to 60 nm, more preferably 32 nm to 55 nm, and even more preferably 35 nm to 50 nm. When the average thickness of the second metal oxide layer is 30 nm or more, the effect of suppressing the transmission of water vapor can be improved. When the average thickness of the second metal oxide layer is 60 nm or less, the total light transmittance can be increased. The average thickness (height) of the second metal oxide layer can be measured, for example, as follows. First, a substrate on which a second metal oxide layer having a predetermined thickness of multiple levels is formed is prepared, and the physical thickness of the second metal oxide layer having a predetermined thickness of multiple levels is measured by a contact step gauge. In addition, the amount of material of the second metal oxide layer in the second metal oxide layer having a predetermined thickness of multiple levels is measured by quantitative analysis using an X-ray fluorescence measurement device (XRF, manufactured by Rigaku Corporation). A calibration curve is created from the film thickness measured by the contact step gauge and the amount of material of the second metal oxide layer measured by quantitative analysis using the X-ray fluorescence measurement device (XRF). In the sample to be actually measured, the amount of material of the second metal oxide layer is quantitatively analyzed using the X-ray fluorescence measurement device (XRF), and the film thickness is calculated using the created calibration curve. Ten samples are similarly created, and the average value is taken as the average thickness.

[0045] The arithmetic mean roughness Ra of the surface of the second metal oxide layer is preferably 15 nm or less, more preferably 11 nm or less, and even more preferably 10 nm or less. When the arithmetic mean roughness Ra of the surface of the second metal oxide layer is 15 nm or less, the moist heat resistance can be improved. The arithmetic mean roughness Ra of the surface of the second metal oxide layer can be measured by an optical interference type surface profile roughness meter (WYKO ContourGT K1M, manufactured by Bruker Japan, measurement conditions: VSI mode). The surface of the second metal oxide layer means the surface of the second metal oxide layer that does not face the metal layer.

[0046] The surface resistance value of only the second metal oxide layer is preferably 10,000 Ω / □ or less, more preferably 5,000 Ω / □ or less, and even more preferably 1,000 Ω / □ or less. The surface resistance can be measured, for example, by forming only the second metal oxide layer on the substrate, measuring any 10 points using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech, model number: MCP-T610), and calculating the average value.

[0047] The method for forming the second metal oxide layer is not particularly limited and can be appropriately selected depending on the purpose. For example, a method in which the entire exposed surface of the metal layer is treated using various sputtering methods, such as DC magnetron sputtering, vapor deposition, ion plating, etc., can be mentioned. When forming the second metal oxide layer, it is preferable to contain hydrogen in the reaction atmosphere during the layer formation in order to prevent the layer (film) from crystallizing over time. By containing hydrogen in the reaction atmosphere, it is possible to obtain a film (layer) in which the second metal oxide layer can maintain an amorphous state even when heat is applied, and a transparent conductive film with excellent moist heat resistance can be obtained.

[0048] <Other layers> The other layers are not particularly limited and may be appropriately selected depending on the purpose. For example, an undercoat layer may be used.

[0049] <<Underlayer>> The underlayer is a layer disposed between the substrate and the first metal oxide layer, and by providing the underlayer, it is possible to obtain effects such as improved adhesion between the substrate and the first metal oxide layer and improved scratch resistance.

[0050] The shape, structure and size of the underlayer are not particularly limited and may be appropriately selected depending on the purpose.

[0051] Examples of the material for the undercoat layer include acrylic resin, ester resin, silicone resin, and organic-inorganic hybrid materials.

[0052] The average thickness of the underlayer is preferably 50 nm or more and 3,500 nm or less, more preferably 70 nm or more and 3,000 nm or less, and even more preferably 80 nm or more and 2,500 nm or less. When the average thickness of the underlayer is 50 nm or more, the adhesion between the substrate and the first metal oxide layer can be improved. When the average thickness of the underlayer is 3,500 nm or less, the total light transmittance can be increased. The average thickness (height) of the underlayer can be measured, for example, as follows. The reflected waveform of the base material on which the underlayer is formed is measured using an ultraviolet-visible spectrophotometer (UV3600, manufactured by Shimadzu Corporation), and the average thickness (height) of the underlayer can be calculated from the spectral shape.

[0053] The arithmetic surface roughness Ra of the surface of the underlayer is not particularly limited and can be appropriately selected depending on the purpose, but a smaller value is preferable. The smaller the arithmetic surface roughness Ra of the surface of the underlayer, the smaller the arithmetic mean roughness Ra of the surfaces of the first metal oxide layer, the metal layer, and the second metal oxide layer formed on the underlayer can be.

[0054] The method for forming the undercoat layer is not particularly limited and may be appropriately selected depending on the purpose. For example, a method in which the entire surface of the base material is treated using wet coating or the like may be mentioned.

[0055] Here, an example of the transparent conductive film of the present invention will be described with reference to the drawings. Fig. 1A is a cross-sectional view showing an example of the transparent conductive film of the present invention, and Fig. 1B is a cross-sectional view showing another example of the transparent conductive film of the present invention. A transparent conductive film 10 shown in FIG. 1A has, on a substrate 11, a first metal oxide layer 12a, a metal layer 13, and a second metal oxide layer 12b, in this order. The transparent conductive film 10 shown in FIG. 1B is similar to the transparent conductive film 10 shown in FIG. 1A except that the transparent conductive film 10 shown in FIG. 1A has an undercoat layer 14 between the substrate 11 and the first metal oxide layer 12a.

[0056] Applications of the transparent conductive film of the present invention include, for example, transparent electrodes for liquid crystal displays, organic EL and inorganic EL lighting, thin-film solar cells, electromagnetic wave shields, window films, electronic blackboards, and transparent heaters. EXAMPLES

[0057] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0058] Example 1 <Manufacture of Transparent Conductive Film 1> NH-1000G (organic-inorganic hybrid resin, manufactured by Nippon Soda Co., Ltd.) was applied by wet coating onto a polyethylene terephthalate film having an average thickness of 125 μm as a substrate, to form an undercoat layer having an average thickness of 1.5 μm. Next, on the underlayer, the pressure during film formation was 0.37 Pa and the input power density was 3.3 W / cm 2 Under introduction of argon gas and oxygen gas (argon:oxygen=95:5), ZTO containing 70 mass % zinc oxide and 30 mass % tin oxide was sputtered to form a first metal oxide layer with an average thickness of 53 nm. Next, on the first metal oxide layer, a deposition pressure of 0.25 Pa and an input power density of 1.5 W / cm 2 Under an introduction of argon gas, a silver alloy containing 89 mass % silver and 11 mass % copper was sputtered to form a metal layer having an average thickness of 11 nm. Next, on the metal layer, the pressure during film formation was 0.35 Pa and the input power density was 3.3 W / cm 2 Under the introduction of argon gas, oxygen gas, and hydrogen gas (argon:oxygen:hydrogen=95.5:3.5:1), ITO containing 90 mass % indium oxide and 10 mass % tin oxide was sputtered to form a second metal oxide layer with an average thickness of 38 nm, and transparent conductive film 1 was obtained.

[0059] Example 2 <Manufacture of Transparent Conductive Film 2> A transparent conductive film 2 was obtained in the same manner as in Example 1, except that in Example 1, the material of the underlayer was changed to Si Coat 801 (silicone resin, manufactured by Momentive Performance Materials Japan, LLC) and an underlayer with an average thickness of 90 nm was formed.

[0060] Example 3 <Manufacture of Transparent Conductive Film 3> Transparent conductive film 3 was obtained in the same manner as in Example 1, except that the material of the undercoat layer was changed to NSC-3162A (silicone resin, manufactured by Nippon Fine Chemicals Co., Ltd.) and an undercoat layer with an average thickness of 1.5 μm was formed.

[0061] Example 4 <Manufacture of Transparent Conductive Film 4> Transparent conductive film 4 was obtained in the same manner as in Example 1, except that in Example 1, "ITO containing 90 mass% indium oxide and 10 mass% tin oxide" was changed to "ITO containing 95 mass% indium oxide and 5 mass% tin oxide."

[0062] Example 5 <Production of Transparent Conductive Film 5> Transparent conductive film 5 was obtained in the same manner as in Example 2, except that in Example 2, "ITO containing 90 mass% indium oxide and 10 mass% tin oxide" was changed to "ITO containing 95 mass% indium oxide and 5 mass% tin oxide."

[0063] Comparative Example 1 <Manufacture of Transparent Conductive Film 6> In Example 1, the conditions for forming the second metal oxide layer were a deposition pressure of 0.37 Pa and an input power density of 3.3 W / cm. 2 and changing the atmosphere to an atmosphere containing argon gas and oxygen gas (argon:oxygen=98:2), the same procedure as in Example 1 was repeated to obtain a transparent conductive film 6.

[0064] Comparative Example 2 <Manufacture of Transparent Conductive Film 7> A transparent conductive film 7 was obtained in the same manner as in Example 2, except that the conditions for forming the second metal oxide layer were changed to the same conditions as in Comparative Example 1.

[0065] Comparative Example 3 <Manufacture of Transparent Conductive Film 8> A transparent conductive film 8 was obtained in the same manner as in Example 3, except that the conditions for forming the second metal oxide layer were changed to the same conditions as in Comparative Example 1.

[0066] Comparative Example 4 <Manufacture of Transparent Conductive Film 9> In Example 1, the conditions for forming the first metal oxide layer and the second metal oxide layer were set as follows: deposition pressure: 0.37 Pa; input power density: 3.3 W / cm 2 A transparent conductive film 9 was obtained in the same manner as in Example 1, except that the composition was adjusted to the above, and ITO containing 90 mass % indium oxide and 10 mass % tin oxide was sputtered under the introduction of argon gas and oxygen gas (argon:oxygen=98:2) so that the average thickness was 43 nm.

[0067] Comparative Example 5 <Production of Transparent Conductive Film 10> A transparent conductive film 10 was obtained in the same manner as in Example 2, except that the conditions for forming the first metal oxide layer and the conditions for forming the second metal oxide layer were changed to the same conditions as in Comparative Example 4.

[0068] Comparative Example 6 <Production of Transparent Conductive Film 11> A transparent conductive film 11 was obtained in the same manner as in Example 3, except that the conditions for forming the first metal oxide layer and the conditions for forming the second metal oxide layer were changed to the same conditions as in Comparative Example 4.

[0069] Comparative Example 7 <Manufacture of Transparent Conductive Film 12> In Example 1, the conditions for forming the first metal oxide layer were a deposition pressure of 0.37 Pa and an input power density of 3.3 W / cm. 2A transparent conductive film 12 was obtained in the same manner as in Example 1, except that the average thickness of the second metal oxide layer was changed to 43 nm, and an ITO containing 90 mass % indium oxide and 10 mass % tin oxide was sputtered under the introduction of argon gas and oxygen gas (argon:oxygen = 98:2) to obtain an average thickness of 43 nm.

[0070] Comparative Example 8 <Manufacture of Transparent Conductive Film 13> A transparent conductive film 13 was obtained in the same manner as in Example 2, except that the conditions for forming the first metal oxide layer and the average thickness of the second metal oxide layer were changed to the same conditions as in Comparative Example 7.

[0071] Comparative Example 9 <Manufacture of Transparent Conductive Film 14> A transparent conductive film 14 was obtained in the same manner as in Example 3, except that the conditions for forming the first metal oxide layer and the average thickness of the second metal oxide layer were changed to the same conditions as in Comparative Example 7.

[0072] Comparative Example 10 <Production of Transparent Conductive Film 15> A transparent conductive film 15 was obtained in the same manner as in Example 1, except that the conditions for forming the first metal oxide layer were changed to be the same as the conditions for forming the second metal oxide layer, and the average thickness of the first metal oxide layer and the second metal oxide layer was changed to 43 nm.

[0073] Comparative Example 11 <Manufacture of Transparent Conductive Film 16> A transparent conductive film 16 was obtained in the same manner as in Example 2, except that the formation conditions and average thickness of the first metal oxide layer and the average thickness of the second metal oxide layer were changed to the same conditions as in Comparative Example 10.

[0074] Comparative Example 12 <Manufacture of Transparent Conductive Film 17> A transparent conductive film 17 was obtained in the same manner as in Example 3, except that the formation conditions and average thickness of the first metal oxide layer and the average thickness of the second metal oxide layer were changed to the same conditions as in Comparative Example 10.

[0075] Comparative Example 13 <Manufacture of Transparent Conductive Film 18> In Example 2, the average thickness of the first metal oxide layer was changed to 55 nm, and further, a deposition pressure of 0.37 Pa and a power density of 3.3 W / cm were applied on the metal layer. 2 A transparent conductive film 18 was obtained in the same manner as in Example 2, except that the composition ratio of the zinc oxide layer to the tin oxide layer was adjusted to 70% by mass, and ZTO containing 70% by mass of zinc oxide and 30% by mass of tin oxide was sputtered under the introduction of argon gas and oxygen gas (argon:oxygen=95:5) to form a second metal oxide layer having an average thickness of 40 nm.

[0076] The average thickness of each layer in the produced transparent conductive film was measured as follows. First, a substrate was prepared on which a first metal oxide layer, a metal layer, or a second metal oxide layer was formed at multiple levels of predetermined thickness, and the physical film thickness of each layer at multiple levels of predetermined thickness was measured using a contact step gauge. In addition, the amount of material of the first metal oxide layer, metal layer, or second metal oxide layer in the first metal oxide layer, metal layer, or second metal oxide layer of multiple levels of specified thickness was measured by quantitative analysis using an X-ray fluorescence measurement device (XRF, manufactured by Rigaku Corporation). A calibration curve was created from the film thickness measured by the contact step gauge and the amount of material in each layer measured by quantitative analysis using an X-ray fluorescence analyzer (XRF). The transparent conductive film was subjected to quantitative analysis using an X-ray fluorescence analyzer (XRF) to detect elements derived from each layer, and the average value of the measurements at 10 points was taken as the average thickness. The average thickness of the first metal oxide layer was determined by detecting the fluorescent X-ray intensity of zinc derived from the first metal oxide layer, the average thickness of the metal layer was determined by detecting the fluorescent X-ray intensity of silver derived from the metal layer, and the average thickness of the second metal oxide layer was determined by detecting the fluorescent X-ray intensity of indium derived from the second metal oxide layer. In addition, for the reflection waveform of the base material forming the base layer, the average thickness of the base layer (height) was calculated by measuring it using an ultraviolet-visible spectrophotometer (UV3600, manufactured by Shimadzu Corporation). For each layer, the average value of the measured values at 10 locations was taken as the average thickness. The results are shown in Tables 1 to 4.

[0077] Also, for the obtained transparent conductive films 1 to 18, the arithmetic surface roughness Ra of the surface of the second metal oxide was measured using an optical interference type surface roughness meter (manufactured by Bruker Japan Co., Ltd., WYKO ContourGT K1M, measurement conditions: VSI mode). The results are shown in Tables 1 to 4.

[0078] Next, the obtained transparent conductive films 1 to 17 were heat-treated in a constant temperature device at 150 °C (device name: DRX420DA, manufactured by ADVANTEC Co., Ltd.) for 30 minutes. After the heat treatment, the crystallinity of the second metal oxide layer in the transparent conductive film was confirmed by the following X-ray crystallography method. For the transparent conductive film 18, since ZTO was used for the second metal oxide layer, the crystallinity of the second metal oxide layer was not confirmed. Specifically, it was confirmed by the following method. First, X-ray crystallography was performed under the following conditions. <Measurement conditions for X-ray crystallography> · Device name: X-ray diffractometer (XRD6100, manufactured by Shimadzu Corporation) · Standard mode · X-ray source: CuKα · Tube voltage: 40 kV · Tube current: 30 mA · Drive axis: 2θ / θ · Scanning speed: 2.00 ° / min · Scanning step: 0.02 ° · Scanning range: Measure the diffraction intensity from 29 ° to 32 ° · Goniometer: Vertical type · Divergence slit: 1 ° · Scattering slit: 1 ° Receiving slit: 0.30mm For transparent conductive films 1 to 17, raw data of the spectra obtained by X-ray crystal diffraction method are shown in Figures 2A to 2Q, respectively. The presence or absence of detection of a peak at 2θ = 29° to 32° corresponding to the (222) plane measured by X-ray crystal diffraction method was judged based on the following method. The results are shown in Tables 1 to 4. Based on the raw measured data, the following values <1> ~ <3> Calculate. <1> Maximum diffraction intensity in the range of 30° to 31° <2> The diffraction intensity at 29° and 32° is added and divided by 2 <3> <1> of <2> Divided by " <1> The "maximum value of the diffraction intensity in the range of 30° to 31°" is higher when the ITO in the second metal oxide layer is crystallized than when the ITO is not crystallized. Also," <1> When the ITO in the second metal oxide layer is not crystallized, the "maximum value of the diffraction intensity in the range of 30° to 31°" is " <2> The value is close to the sum of the diffraction intensities at 29° and 32° divided by 2. In this embodiment, <3> <1> of <2> If the value of "Divide by" is 1.2 or more, it is judged that "a peak has been detected" and <3> <1> of <2> When the value obtained by dividing the total by the mean value was less than 1.2, it was determined that "no peak was detected." In addition, in Tables 1 to 4, "ITO (amorphous)" means that the ITO did not crystallize even after heat treatment at 150°C for 30 minutes, and no X-ray diffraction peak was detected, and "ITO (microcrystalline)" means that the ITO crystallized by heat treatment at 150°C for 30 minutes, and an X-ray diffraction peak was detected.

[0079] Next, the obtained transparent conductive film was subjected to a moist heat resistance test as follows. [Heat and humidity resistance test] Two sheets each of the obtained transparent conductive films 1 to 18 were prepared, and one of the transparent conductive films was subjected to a moisture and heat resistance test in which it was left standing for 250 hours in a thermo-hygrostat at 60°C and 95% RH, and the other was subjected to a moisture and heat resistance test in which it was left standing for 250 hours in a thermo-hygrostat at 85°C and 85% RH.

[0080] After the moist heat resistance test, the transparent conductive films 1 to 18 were evaluated for "appearance evaluation," "conductivity (surface resistance measurement)," "transparency (total light transmittance)," and "adhesion (cross-cut peel test)" as follows. The results are shown in Tables 1 to 4.

[0081] <Appearance evaluation> The transparent conductive film after the moist heat resistance test was visually inspected for appearance, and the occurrence of silver aggregation (silver agglomerates) in the metal layer was evaluated based on the following evaluation criteria. The results are shown in Tables 1 to 4. Examples of photographs in plan view of Example 1 are shown in FIG. 3A (60° C., 95% RH, 250 hours) and FIG. 3B (85° C., 85% RH, 250 hours), and examples of photographs in plan view of Comparative Example 5 are shown in FIG. 3C (60° C., 95% RH, 250 hours) and FIG. 3D (85° C., 85% RH, 250 hours). White dots in the photographs indicate silver agglomerates. If the evaluation result under the moist heat resistance test conditions "60° C., 95% RH, 250 hours" is 3 or more, and the evaluation result under the condition "85° C., 85% RH, 250 hours" is 2 or more, it is at a level that does not cause any problems in practical use. [Evaluation Criteria] 3: There are three or fewer silver agglomerates with a diameter of 0.5 mm or more in an area of ​​40 mm x 40 mm. 2: There are 4 to 10 silver agglomerates with a diameter of 0.5 mm or more in an area of ​​40 mm x 40 mm 1: There are 10 or more silver agglomerates with a diameter of 0.5 mm or more in an area of ​​40 mm x 40 mm.

[0082] <Conductivity (surface resistance measurement)> The surface resistance of the transparent conductive film was measured "before the moist heat resistance test" and "after the moist heat resistance test". The surface resistance was measured at 10 arbitrary points using a low resistivity meter (manufactured by Mitsubishi Chemical Analytech, model number: MCP-T610), and the average value was taken as the surface resistance value. The measurement results were evaluated according to the following evaluation criteria. The worse evaluation result of the evaluation results for each condition of the moist heat resistance test ("60°C, 95% RH, 250 hours" and "85°C, 85% RH, 250 hours") was taken as the evaluation of the transparent conductive film. Note that if the evaluation result for each condition of the moist heat resistance test is "◯", it is at a level that does not pose any problems in practical use. [Evaluation Criteria] ○: Surface resistance is 30Ω / □ or less ×: Surface resistance is over 30Ω / □

[0083] <Transparency (total light transmittance measurement)> The total light transmittance of the transparent conductive film was measured before and after the moist heat resistance test. The total light transmittance was measured using a haze meter (manufactured by Nippon Denshoku Industries Co., Ltd., model number: NDH5000SP) in accordance with JIS K7361-1 / HAZE:JIS K7136.

[0084] <Adhesion (checkerboard peel test)> The transparent conductive film "before the moist heat resistance test" and "after the moist heat resistance test" were evaluated for adhesion by a cross-cut peel test. Specifically, 11 cuts were made at equal intervals (1.5 mm) from the second metal oxide layer side, then turned 90° and made another 11 cuts at equal intervals (1.5 mm) to create 100 squares cut into a 10 x 10 grid pattern. On top of this, cellophane tape (product number: CT405AP-18, manufactured by Nichiban Co., Ltd.) was applied to adhere to the second metal oxide layer. Then, the edge of the tape was held and the tape was instantly peeled off in a direction perpendicular to the laminated surface, and the peeling state of the second metal oxide was confirmed. The results are shown in Tables 1 to 4. In the results, the numerators represent the number of remaining masses that did not peel off, and 100 / 100 represents a state where no peeling occurred. The measurement results were evaluated according to the following evaluation criteria. The worse evaluation result of the evaluation results under each condition of the moist heat resistance test ("60°C, 95% RH, 250 hours" and "85°C, 85% RH, 250 hours") was used as the evaluation of the transparent conductive film. An evaluation result of 2 or more is at a level that does not pose a problem in practical use. [Evaluation Criteria] 3: The number of remaining squares is 100 / 100 2: The number of remaining squares is between 90 / 100 and 100 / 100 1: Less than 90 / 100 squares remaining

[0085] [Table 1]

[0086] [Table 2]

[0087] [Table 3]

[0088] [Table 4]

[0089] The results in Tables 1 to 4 show that the transparent conductive films of Examples 1 to 5 can maintain excellent appearance, conductivity, total light transmittance, and adhesion even after the moist heat resistance test. Furthermore, from the results of Figures 2A to 2C and Figures 2P to 2Q, it was shown that Examples 1 to 3, in which the tin oxide content in the second metal oxide layer is 10 mass% relative to the total amount of indium oxide and tin oxide, are less susceptible to crystallization than Examples 4 and 5, in which the tin oxide content is 5 mass% relative to the total amount of indium oxide and tin oxide, because fewer peaks were detected at 2θ=29° to 32° corresponding to the (222) plane in X-ray diffraction measurement. [Explanation of symbols]

[0090] 10 Transparent conductive film 11 Base material 12a First metal oxide layer 12b Second metal oxide layer 13 Metal layer 14 Base layer

Claims

1. A transparent conductive film having a substrate, a first metal oxide layer, a metal layer, and a second metal oxide layer in this order, the first metal oxide layer contains zinc oxide and tin oxide; The metal layer contains at least one of silver and a silver alloy, the second metal oxide layer contains indium oxide and tin oxide; a content of the indium oxide and the tin oxide in the second metal oxide layer is 95 mass% or more with respect to a total amount of the second metal oxide layer; a content of the tin oxide in the second metal oxide layer is 5 mass% or more and 14 mass% or less with respect to a total amount of the indium oxide and the tin oxide, The transparent conductive film is characterized in that, when the transparent conductive film is heat-treated at 150° C. for 30 minutes and then measured by an X-ray crystal diffraction method, no peak is detected at 2θ=29° to 32°.

2. The transparent conductive film according to claim 1 , wherein the second metal oxide layer has an arithmetic mean roughness Ra of 15 nm or less.

3. A transparent conductive film described in any one of claims 1 to 2, which has a total light transmittance of 82% or more measured in accordance with JIS K7361-1.

Citation Information

Patent Citations

  • Remote controller

    JP1989051897A

  • Transparent electrode

    JP2002015623A

  • Oxide sintered compact, spattering target, and transparent conductive thin film

    JP2005320192A

  • Oxide sintered compact, oxide film using same and laminate comprising the oxide film

    JP2007112673A

  • Gas barrier laminate

    JP2020082660A